FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PERAWAT DI RSUD BANGKINANG TAHUN 2019 - Rizki Rahmawati Lestari; Sabri Afandi Afandi (Universitas Pahlawan, 2019)
Fatigue is a physical and psychological condition that is tired or tired because of work, this can be felt directly by the body and can be seen what they are experiencing. And then every nurse who is experiencing work fatigue can be sure that the performance will not be maximal to the patient's recovery and also reduces the nurse's productivity in providing services. The purpose of this study was to determine the factors associated with work fatigue at the 2019 Bangkinang District Hospital. This type of research is quantitative analytic with cross sectional design. This research was conducted on 17-24 June 2019. The population in this study were nurses in Bangkinang District Hospital, which numbered 131, with a sample of 95 people obtained using simple random sampling technique. Data collection techniques using questionnaires as well as measuring the height and weight of nurses. Analysis of the data used is univariate and bivariate analysis with Chi Square test. The results showed there was a significant relationship between sex, age, and nutritional status with work fatigue in nurses where the value (P value = 0.016) gender, POR = 3.87, value (P value = 0.000) age, POR = 6 , 94, value (P value = 0.001) nutritional status, POR = 5.37. It is expected that nurses will control their nutritional status by increasing food intake to minimize work fatigue.